EXPERIMENTAL CADMIUM CHLORIDE-INDUCED AGE-RELATED MORPHOLOGICAL CHANGES OF JEJUNUM - Ружицька, О.Ю. (World of Medicine and Biology, 2015)
The investigation of jejunum wall morphological status and morphometric analysis in different ages white rats under the influence of cadmium chloride was performed in the experiment. Established that due to the toxic effect of cadmium chloride undergoes significant microscopic, electronmicroscopic and morphometric changes of all structural components shells jejunum, which are more prominent in immature animals.